The Role of the Song “Beranjak Dewasa” in Supporting the Process of Self-Acceptance During Adolescent Transition - Elvia Inayatul Aini Ranjani; Dedet Erawati (CV. Syntax Corporation Indonesia, 2026)
The transition from adolescence to adulthood is a developmental phase marked by emotional changes, identity exploration, and social pressure, which may lead to anxiety and difficulties in self-acceptance. In this context, music can serve as a reflective medium that helps adolescents understand their inner experiences. This study aims to analyze the role of the song “Beranjak Dewasa” by Nadin Amizah in supporting the process of self-acceptance among adolescents through intrapersonal communication. This research employs a qualitative approach, using participant observation, in-depth semi-structured interviews with adolescents aged 17–20 in Cirebon City, as well as song lyric analysis and supporting documentation. The theoretical framework is based on Jalaluddin Rakhmat’s intrapersonal communication theory and Christopher Germer’s concept of self-acceptance. The findings indicate that the song “Beranjak Dewasa” functions as an emotional stimulus that initiates intrapersonal communication through the stages of sensation, perception, memory, and thinking. This process encourages self-awareness, acceptance of personal imperfections, and the development of a more positive internal dialogue among adolescents. The song is not merely perceived as entertainment but also as a medium for self-reflection that assists adolescents in coping with anxiety and the demands of growing up. Therefore, reflective songs such as “Beranjak Dewasa” have significant potential as educational and psychological tools that support adolescents’ self-acceptance during the transition to adulthood.